Experimental study of the sensible heat storage in the water/TiO2 nanofluid enclosed in an annular space. (25th July 2017) - EL-Kaddadi, Latifa; Asbik, Mohamed; Zari, Nadia; Zeghmati, Belkacem
Highlights: Experimental study of the sensible heat storage cycle in specific nanofluid is presented. Effects of nanofluid mass concentration and the HTF mass flow rate on thermal behavior are investigated. Natural convection causes the thermal stratification in the nanofluid. The stored heat flux density increases with the nanoparticles mass concentration. Abstract: This article is devoted to an experimental study of heat transfer during a sensible heat storage cycle (charging/discharging) in a vertical cylindrical system. The experimental setup consists of two cylindrical tanks filled respectively with hot and cold water, a test bench, and measurement instruments. The test bench, thermally insulated with glass wool, is also composed of two vertical concentric tubes whose annular space contains the used nanofluid (the mixture of distilled water and titanium dioxide nanoparticles). The heat transfer fluid (HTF) flows in the upward direction of the inner tube (HTF pipe). Adequate methods were used to prepare titanium dioxide nanoparticles for which the diameter is less than 20 nm. Both convective heat transfer coefficient between external inner tube wall and nanofluid, and heat flux densities during storage cycle, were evaluated. The effect of nanofluid mass concentration (0.005, 0.01, 0.02 and 0.03 wt%) and the HTF mass flow rate on thermal heat transfer coefficient and hence heat flux densities were analyzed. Experimental results show that the average convective heat transfer coefficient increases with increasing the mass flow rate, and it is improved by comparison with the fluid base (distilled water) when the nanofluid is considered. Furthermore, it has been observed that there is an optimal nanoparticles mass concentration corresponding to a maximal average convective heat flux and also a maximal recovered heat flux density. Consequently, convective heat transfer coefficient has a strong influence on the sensible heat during a storage cycle (charging/discharging).